Impact of Networks on Innovative Development of Companies in Lubelskie Region - Dolińska, Małgorzata (Wpływ sieci na rozwój innowacyjny przedsiębiorstw w regionie lubelskim, 2010)
For an enterprise, innovation is key to creating a competitive advantage on the market and a superior customer value. Development of innovation market and the implementation of EU innovation policy in our state should be conducive to increasing the activity of the companies in cooperating with their partners in innovation processes in the forthcoming years. Our goal in this paper is to assess the results of questionnaire research on the role of company cooperation with partners and consumers during innovation process execution in the network. This research was carried out in Lubelskie region companies in 2009.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 437-445
Keywords: networks of innovators; research in Lubelskie region